Magnetic ion-exchange (MIEX) resin for perfluorinated alkylsubstance (PFAS) removal in groundwater: Roles of atomic charges for adsorption. (15th August 2020) - Park, Minkyu; Daniels, Kevin D.; Wu, Shimin; Ziska, Austin D.; Snyder, Shane A.
Abstract: In this study, magnetic ion exchange (MIEX) resin was evaluated to remove six carboxylic and three sulfonic PFAS at environmentally relevant concentrations (∼300 ng/L) in groundwater with low organic content and aromaticity (0.78 mg/L of dissolved organic carbon, DOC and 0.96 L mg −1 m −1 of specific UV absorbance, SUVA). In order to evaluate PFAS adsorption, the apparent equilibrium constant for PFAS adsorption in a dilute system was derived as an indicator of the adsorption capacity of MIEX. In adsorption of PFAS, hydrophobic interactions induced by difluoromethylene and trifluoromethyl groups are known to be effective. However, the hydrophobic and charge interactions caused by such functional groups are not easily differentiable from each other since both are additive with respect to the chain length. In this study, the total negative atomic charge [∑ Q i (−)] was calculated using density functional theory (DFT) calculation and correlated with the apparent equilibrium constants. The negative atomic charge showed better correlation than the hydrophobicity (log D ow at pH 7) of PFAS, suggesting that the charge interaction would be a more plausible role of fluorinated moieties for adsorption in the MIEX process than the hydrophobic interaction. This was also bolstered by the similar adsorption kinetics and equilibrium of PFOS (log D ow = 3.05) and its less hydrophobic isomer (log D ow = 2.79), but with almost identical total negative atomic charge (8.05 and 8.06 of ∑ Q i (−), respectively). The regeneration efficiency of MIEX was also assessed. Almost complete restoration of PFAS adsorption capacity was achieved after 30 min of a regeneration process with a 10% w/w NaCl solution as a regenerant. The efficient regeneration was attributed to the effective desorption of dissolved organic matter that occupied sorptive sites predominantly. Graphical abstract: Image 1 Highlights: MIEX was evaluated for the attenuation of ∼300 ng/L PFAS in groundwater. Sulfonic PFAS were removed better than carboxylic ones with the same chain length. Apparent equilibrium constant requiring only one fitting parameter was derived. Total negative atomic charge was correlated with adsorption equilibrium constants. Fast regeneration of MIEX due to effective desorption of DOM.